The ethnobotanical, bioactive compounds, pharmacological activities and toxicological evaluation of garlic (Allium sativum): A review - Benedict Chukwuebuka Okoro; Titilope Modupe Dokunmu; Esther Okafor; Ibukunoluwa Adedoyinsola Sokoya; Emmanuel Nsedu Israel; Daniel Oluwaremilekun Olusegun; Mercy Bella-Omunagbe; Uche Miracle Ebubechi; Eziuche Amadike Ugbogu; Emeka Eze Joshua Iweala (Elsevier, 2023)
Background: Garlic (Allium sativum) is a medicinal plant exploited for its diverse pharmacological benefits and used as a cooking spice globally. In traditional Chinese medicine, garlic is prepared and served in different forms such as syrup, extract, decoct, garlic oil, tincture, and infusion, and they are exploited for their medicinal benefits in the treatment of several diseases such as food poisoning, cholera, fever, headache, dysentery, lowering blood pressure, and as a stimulant, diuretic, expectorant, and diaphoretic agent. Objectives: This study reviewed the ethnomedicinal uses, bioactive compounds, pharmacological activities, and toxicological evaluation of garlic. Method: Literature searches were carried out on the following databases: PubMed, Frontiers, Science Direct, Springer, Wiley, and MDPI databases. Chemical structures identified in garlic were drawn using ChemDraw (version 12.0.2) after a thorough search in PubChem databases, the NIST Chemistry Webbook, and ChemSpider. ''Allium sativum'', ''garlic'', ''Allium sativum pharmacological'', ''Allium sativum ethnomedicine'', ''Allium sativum bioactive compounds'', and other similar keywords were used to search for relevant journals and contents. Results: The plant is a rich source of carbohydrate, minerals, fat, vitamins, fibers, and phenolic compounds that promote good health. The sulfur-containing bioactive compounds extracted from garlic include Allicin, Vinyl-4H-1, 3-dithiin, E-Ajoene, Diallyl trisulfide, Alliin, Allyl methyl sulfide, 2-Diallyl sulfide, Z-Ajoene, Diallyl disulfide, Quercetin, Allyl mercaptan, Allyl propyl disulfide, Thiacremonone, Allyl methyl trisulfide, and Gamma-glutamylcysteine. Several in vitro and in vivo studies have reported that garlic and its bioactive constituents have several pharmacological activities, including anti-inflammatory, anticancer, antidiabetic, antihypertensive, anti-obesity, antimicrobial, antioxidant, antithrombotic, and anti-Alzheimer activities. Conclusion: This study suggested the effective use of garlic in treating various diseases, which may be attributed to the presence of bioactive compounds in the plant. Additionally, its powerful antioxidant action also contributes to reducing the harm that oxidative stress causes to critical biomolecules in the body which helps in disease prevention. The presence of bioactive compounds in garlic can be exploited by the food and pharmaceutical industries for the development of therapeutic and food products. However, more comprehensive studies in human clinical trials are needed to validate safe and effective doses for the use of garlic for treating several diseases.